2015
DOI: 10.15252/embr.201540096
|View full text |Cite
|
Sign up to set email alerts
|

The thymic cortical epithelium determines the TCR repertoire of IL ‐17‐producing γδT cells

Abstract: The thymus provides a specialized microenvironment in which distinct subsets of thymic epithelial cells (TECs) support T-cell development. Here, we describe the significance of cortical TECs (cTECs) in T-cell development, using a newly established mouse model of cTEC deficiency. The deficiency of mature cTECs caused a massive loss of thymic cellularity and impaired the development of abT cells and invariant natural killer T cells. Unexpectedly, the differentiation of certain cdT-cell subpopulations-interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 70 publications
2
45
1
Order By: Relevance
“…IL-17-producing γδT (γδT17) cells are predominantly generated in fetal and newborn thymus (33, 34). Two recent studies have revealed that thymic epithelial cells may foster a thymic environment for temporal control of γδT17 differentiation (22, 35) and that such temporal control of γδT17 differentiation requires mTORC1 in TECs (22). γδT17 cells mainly reside in the CD44 + CD27 − population, while IFNγ-producing γδT (γδT1) cells are enriched in the CD27 + population (34).…”
Section: Resultsmentioning
confidence: 99%
“…IL-17-producing γδT (γδT17) cells are predominantly generated in fetal and newborn thymus (33, 34). Two recent studies have revealed that thymic epithelial cells may foster a thymic environment for temporal control of γδT17 differentiation (22, 35) and that such temporal control of γδT17 differentiation requires mTORC1 in TECs (22). γδT17 cells mainly reside in the CD44 + CD27 − population, while IFNγ-producing γδT (γδT1) cells are enriched in the CD27 + population (34).…”
Section: Resultsmentioning
confidence: 99%
“…Somewhat paradoxically, cortical thymic epithelial cells (cTECs) are the major IL-7-producing thymic stromal cells, and they do not increase production in the absence of Aire [(Ribeiro et al, 2013) and data not shown]. But mice lacking cTECs due to a spontaneous mutation of β5t have a robust IL-17A-expressing Vγ6 + thymocyte compartment (Nitta et al, 2015). Thus, we infer that mTEC-produced IL-7 is acting locally.…”
Section: Discussionmentioning
confidence: 99%
“…TAGAP −/− mice were generated using the CRISPR/Cas9 genome editing system. Single‐guide (sg) RNA‐targeting TAGAP (5′‐gacccagagaagtcggatgaagg‐3′) was synthesized and cloned into the sgRNA expression vector (Operon Biotechnologies, Tokyo, Japan) as previously described 30 . The sgRNA (50 ng μl −1 ) and hCas9 mRNA (100 ng μl −1 ) were co‐injected into the cytoplasm of pronuclear fertilized eggs, and the eggs were subsequently transferred into the oviducts of pseudopregnant female ICR mice.…”
Section: Methodsmentioning
confidence: 99%